Laporan Keuangan Sebagai Alat Untuk Mengukur Kinerja Keuangan Pada PT. Starfood Di Lamongan - Nur Rahmadhany (UMSurabaya Publishing, 2023)
ABSTRACKTo find out the actual development of a company, it can be seen whether the company's performance is good or not. The purpose of this study is to determine the financial performance of PT. Starfood based on liquidity ratio, solvency ratio, profitability and activity ratio. Analysis of the company's performance which includes the analysis of several financial ratios using a descriptive test. The data collection used in this study is the documentation method. Based on the analysis results: (a) liquidity ratios that the Current Ratio and Quick Ratio from 2017 to 2019 are in a good position, while the Cash Ratio is in a poor position; (b) Judging from the financial performance report of PT. Starfood in Lamongan, it can be seen that the solvency ratio from the results of the Debt Ratio and Debt to Equity is decreasing every year; (c) Stating from the financial performance report of PT. Starfood in Lamongan, it can be seen that the Profitability ratio as a result of the calculation of the ROA and ROE ratio for the 2017 to 2018 period has increased while to 2019 period has decreased. However, NPM and GPM have increased every year and (d) the activity ratio seen in Inventory Turnover, Receivable Turnover, and Total Assets Turnover show a decrease every year. Keywords: Liquidity Ratio, Solvency Ratio, Profitability Ratio, Activity Ratio.